Transitivity and Bidirectional Framing in Telecommunication Advertisements - Fredrick Friday John; Oluwadamilare Daniel Atolagbe (Randwick International of Education and Linguistics Science Journal, 2021)
Advertisements are onerous ways of representing the identity of producers and consumers who are both agents of social life, and mobile telecommunication advertisement is not an exception. However, this has not attracted sufficient attention in linguistic studies. This study investigates the bidirectional framing of the identities of telecommunication service providers and the subscribers in twelve MTN and GLO advertisements, aired on popular mainstream television stations between 2014 and 2017. These were downloaded from youtube, where they are trended as unsolicited adverts to reach millions of users. The qualitative analytical approach was adopted, using transitivity, in the systemic functional linguistic (SFL) framework, as theory, to analyse transcribed texts from the advertisements. The findings show that copywriters use material, mental, verbal, relational and existential processes to frame service providers as welfarists, supremacists and benefactors/beneficiaries, and the subscribers as consumerists, opportunists and beneficiaries/benefactors. The supremacist’ and welfarist’ identities are used as indexes to establish the stiff competition between and among service providers to gain more subscribers. The results also show that welfare services are initiated as basis for out-doing self and other-self services. The enthusiasm of the subscribers to use services account for their framing as ‘consumerists’ and ‘opportunists.’ The beneficiary and benefactor identities are bidirectional, as both service providers, and subscribers mutually benefit from each other in a one-to-one relation. The study concludes that transitivity processes are indelible linguistic resources used in telecommunication advertisement to bidirectionally frame the identities of service providers and subscribers, with a view to enhancing consumerism.